2019
DOI: 10.1556/1886.2019.00004
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis detection in female specimens with cobas® TV/MG for use on the cobas® 6800/8800 systems

Abstract: Trichomoniasis, a common curable sexually transmitted infection caused by the protozoan Trichomonas vaginalis (TV), is usually asymptomatic. However, symptomatic women may experience vaginal discharge and/or vulvar irritation. This study evaluated cobas ® TV/ Mycoplasma genitalium (MG) (Conformité Européene marking for in vitro diagnostic medical devices [CE-IVD]) against other nucleic acid amplification tests (NAATs) for detecting TV in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In this study, the cobas assay was highly sensitive and specific for the detection of T. vaginalis in both male and female urogenital samples, with sensitivities greater than or similar to those seen with other NAATs for T. vaginalis ( 7 , 9 , 12 , 20 , 21 ). The sensitivity and specificity of cobas, when compared to the PIS, showed that male urine samples and female vaginal swab samples are preferred for detection of T. vaginalis infection.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, the cobas assay was highly sensitive and specific for the detection of T. vaginalis in both male and female urogenital samples, with sensitivities greater than or similar to those seen with other NAATs for T. vaginalis ( 7 , 9 , 12 , 20 , 21 ). The sensitivity and specificity of cobas, when compared to the PIS, showed that male urine samples and female vaginal swab samples are preferred for detection of T. vaginalis infection.…”
Section: Discussionsupporting
confidence: 52%
“…Regarding the detection of M. genitalium, the sensitivity of the cobas MG/TV kit was 96.6% in female vaginal swabs and was 100% in male urine samples, while the specificity was 97.0% and 97.6%, respectively [9]. In addition, a study on 1648 female samples reported an overall sensitivity of 100% and a specificity of 99.5% for T. vaginalis detection [10].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostics, Luxembourg). The performance of the kits for C. trachomatis, N. gonorrhoeae, M. genitalium and T. vaginalis detection was compared to that of the cobas CT/NG and TV/MG kits (Roche Diagnostics, USA) [5][6][7][8][9][10]. For the two kits that also detect U. urealyticum, U. parvum and M. hominis, the detection performance was compared to that of published in-house TaqMan PCRs [11,12].…”
mentioning
confidence: 99%
“…Participants will self-collect an additional vaginal specimen for chlamydia, gonorrhoea and trichomonas nucleic acid amplification testing on the Roche Cobas 6800 platform. 29 30 Standard-of-care HIV testing data will be obtained from participants’ electronic medical records at their respective gender health clinic, with written permission. HIV-positive TGM will be excluded as some studies have associated those with HIV having a more diverse vaginal microbiota, 31–33 although effective antiretroviral therapy 34 and regular BV testing and treatment 35 could moderate this risk.…”
Section: Methodsmentioning
confidence: 99%
“…REDCap is a secure, web-based software platform designed to support data capture for research studies, providing an intuitive interface for validated data capture, audit trails for tracking data manipulation and export procedures, automated export procedures for seamless data downloads to common statistical packages, and procedures for data integration and interoperability with external sources. Participants will self-collect an additional vaginal specimen for chlamydia, gonorrhoea and trichomonas nucleic acid amplification testing on the Roche Cobas 6800 platform 29 30. Standard-of-care HIV testing data will be obtained from participants’ electronic medical records at their respective gender health clinic, with written permission.…”
Section: Methodsmentioning
confidence: 99%